A firefly algorithm for solving competitive location-design problem: A case study - Seyed Jafar Sadjadi; Milad Gorji Ashtiani; Reza Ramezanian; Ahmad Makui (Journal of Industrial Engineering International, 2016)
This paper aims at determining the optimal number of new facilities besides specifying both the optimal location and design level of them under the budget constraint in a competitive environment by a novel hybrid continuous and discrete firefly algorithm. A real-world application of locating new chain stores in the city of Tehran, Iran, is used and the results are analyzed. In addition, several examples have been solved to evaluate the efficiency of the proposed model and algorithm. The results demonstrate that the performed method provides good-quality results for the test problems.
Keywords: 650; Competitive facility location; Location design; Market share; Budget constraint; Firefly algorithm